BS EN 50397-2. Covered conductors for overhead lines and the related accessories for rated voltages above 1 kV a.c. and not exceeding 36 kV a.c. Part 2. Accessories for covered conductors. Tests and acceptance criteria (13th August 2021) - British Standards Institution,
No abstract available